With or without a computer? Do you want to play with me? - Oliveira, A.; Dias, R. (Mediterranean Journal of Social Sciences, 2014)
The new technologies are increasingly crucial in all areas. The computer and other technological devices, the communication and information systems, can bring us great benefits, facilitating and streamlining many of our common tasks and activities. We highlight the importance of computer in learning and, particularly, in leisure/recreational activities. In what extent children prefer to play, and communicate, via computer, tablet or other device? Do they easily dispense technological means, choosing to play in social interaction and direct contact? Do they prefer to be at home, at school, at the park or in another natural environment? We intend to verify the importance that children attribute to the computer and how they like to use it, either in the context of learning, retrieving information, doing homework, or in recreational terms. The major objective of this work is to verify to what extent the computer is important in the personal, emotional and social development of children, by the way they use it in their duties, games and daily interactions. We conducted an exploratory study with a population of boys and girls, attending the first four years of schooling. Data were collected within the scope of focus groups and individual interviews. Most children consider that the computer is significant both in study as in the interaction with friends, and many prefer to be online, playing games or exploring virtual worlds, than being offline, doing any sport, talking or hanging out with friends, in outdoor activities. The way children represent and use the computer, help us to better understand the risks they run and the benefits that virtual worlds offer.